Application of minimum quantity lubrication with addition of water in the grinding of alumina - Lopes, Jose C. [UNESP]; Ventura, Carlos E. H.; Rodriguez, Rafael L. [UNESP]; Talon, Anthony G. [UNESP]; Volpato, Roberta S. [UNESP]; Sato, Bruno K. [UNESP]; Mello, Hamilton J. de [UNESP]; Aguiar, Paulo R. de [UNESP]; Bianchi, Eduardo C. [UNESP] (Springer, 2018)
Among the alternatives to reduce the application of cutting fluid in machining industry, minimum quantity lubrication (MQL) technique has been promising, although it can impair cooling properties and the ability of the fluid to penetrate the cutting region. In order to further reduce the quantity of oil and to improve the characteristics of the cooling lubrication method, this work aims to compare the effect of MQL with different ratios of oil/water (1:1, 1:3, and 1:5) on the performance of plunge cylindrical grinding of alumina. Lubricating effect and effective penetration of fluid in the cutting zone are considered the most relevant factors. The lowest surface roughness value was obtained with the application of conventional flood cooling, followed by MQL 1:1. In comparison to conventional MQL technique, reduced surface roughness and grinding wheel wear could be obtained by applying MQL with water.
Keywords: Plunge grinding; Alumina; Minimum quantity lubrication